A Scroll of One’s Own?: Scribal, Philological, and Literary Aspects of 4QIsak (4Q64) - Mizrahi, Noam (Maarav, 2024)
The paper offers a new investigation of a fragmentary Isaiah scroll from Qumran Cave 4, 4QIsak (4Q64), which contains Isa 28:26-29:9. A new material reconstruction of the surviving fragments leads to a detailed evaluation of the scribal properties of the manuscript. The philological analysis of its text vis-à-vis the MT and the other textual witnesses takes into consideration the literary structure and rhetorical design of the prophetic units, leading to some conclusions concerning the nature of this specific scribal artifact and its place within the textual history of Isaiah.